An interplay between BRD4 and G9a regulates skeletal myogenesis - Yang, Naidi; Das, Dipanwita; Shankar, Shilpa Rani; Goy, Pierre-Alexis; Guccione, Ernesto; Taneja, Reshma (Frontiers in Cell and Developmental Biology, 2022)
Histone acetylation and methylation are epigenetic modifications that are dynamically regulated by chromatin modifiers to precisely regulate gene expression. However, the interplay by which histone modifications are synchronized to coordinate cellular differentiation is not fully understood. In this study, we demonstrate a relationship between BRD4, a reader of acetylation marks, and G9a, a writer of methylation marks in the regulation of myogenic differentiation. Using loss- and gain-of-function studies, as well as a pharmacological inhibition of its activity, we examined the mechanism by which BRD4 regulates myogenesis. Transcriptomic analysis using RNA sequencing revealed that a number of myogenic differentiation genes are downregulated in Brd4-depleted cells. Interestingly, some of these genes were upregulated upon G9a knockdown, indicating that BRD4 and G9a play opposing roles in the control of myogenic gene expression. Remarkably, the differentiation defect caused by Brd4 knockdown was rescued by inhibition of G9a methyltransferase activity. These findings demonstrate that the absence of BRD4 results in the upregulation of G9a activity and consequently impaired myogenic differentiation. Collectively, our study identifies an interdependence between BRD4 and G9a for the precise control of transcriptional outputs to regulate myogenesis.